Tra Clara Janés e Mariarosa Scaramuzza (Materiali di Estetica. Terza serie, 2024)
This article serves as a tribute to Clara Janés, a distinguished living Spanish poet, and honors Mariarosa Scaramuzza on the tenth anniversary of her death. Clara Janés, born in Barcelona in 1940 and a member of the Real Academia Española de la Lengua, is celebrated for her extensive literary contributions, including poetry collections and translations. The text reflects on her work, notably ‘El viaje a la luna,’ and her connections with deeply meaningful Tuscan landscapes in ‘Peregrinaje.’ Mariarosa Scaramuzza, a profound interpreter of Janés’ work, authored several critical analyses and translations, enhancing the understanding and appreciation of Janés’ poetry in Italy. The article encapsulates the intellectual and cultural exchange between these two eminent figures, highlighting their shared dedication to poetry’s existential themes.
Keywords: existential themes; Spanish poetry; Clara Janés